Pollen morphology of Artemisia L. (Asteraceae) in Turkey and its systematic value - Kursat, Murat; Civelek, Semsettin; Baser, Birol; Ozbey, Fahrettin; Emre, Irfan (Taylor & Francis Ltd, 2023)
The objective of the current investigation is to use scanning electron and light microscopy to obtain pollen morphological information for all Artemisia taxa growing in Turkey. In addition, statistical analyses were performed and a dichotomous key was prepared for the identification of taxa using pollen characters. Pollen grains of Artemisia are radially symmetrical, isopolar, oblate-spheroidal, and prolate-spheroidal, with the polar axis ranging from 15.23-27.20 mu m. The equatorial diameter ranges from 16.48-27.47 mu m. Artemisia taxa typically have tricolporate, tricolpate pollen. However, pantocolporate, pantocolpate, and syncolporate pollen grains are rarely present in A. austriaca and A. armeniaca. Our study showed that, although other Artemisia taxa have an ornamentation that is microechinate-granulate, A. incana, A. taurica var. vanensis, and A. spicigera differ by their microechinate ornamentation. Furthermore, we found that A. chamaemelifolia contains the highest number of microechinae per 25 mu m(2), whereas A. fragrans had the fewest. Additionally, the average number of granules differs between taxa. The number of granules per 25 mu m(2) is the highest in A. scoparia and the lowest in A. santonicum subsp. santonicum. Furthermore, the UPGMA (unweighted pair group method with arithmetic mean) dendrogram indicated that there are three different groups of taxa based on pollen morphological characteristics from 26 taxa. The average number of granules per 25 mu m(2), as determined by the principal component analysis, plays a significant role in this classification scheme.
Keywords: Artemisia taxa; LM; palynology; SEM; UPGMA